2011
DOI: 10.1111/j.1463-1326.2010.01332.x
|View full text |Cite
|
Sign up to set email alerts
|

Oral magnesium supplementation reduces insulin resistance in non-diabetic subjects - a double-blind, placebo-controlled, randomized trial

Abstract: The incidence of insulin resistance and metabolic syndrome correlates with the availability of magnesium (Mg). We studied the effect of oral Mg supplementation on insulin sensitivity and other characteristics of the metabolic syndrome in normomagnesemic, overweight, insulin resistant, non-diabetic subjects. Subjects were tested for eligibility using oral glucose tolerance test (OGTT) and subsequently randomized to receive either Mg-aspartate-hydrochloride (n = 27) or placebo (n = 25) for 6 months. As trial end… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

7
103
0
4

Year Published

2011
2011
2018
2018

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 157 publications
(114 citation statements)
references
References 12 publications
7
103
0
4
Order By: Relevance
“…Magnesium is essential for insulin secretion, post-receptor insulin signalling, and the glycolytic pathway [1]. The efficacy of magnesium supplementation in improving glycemic control among non-diabetics [30, 31], pre-diabetics [32-34] and diabetics [23, 35, 36] has been suggested in some trials. A recent meta-analysis documented that magnesium is effective in decreasing the HOMA-IR index ( P = 0.013) but has no effect on glucose, HbA1c or insulin.…”
Section: Discussionmentioning
confidence: 99%
“…Magnesium is essential for insulin secretion, post-receptor insulin signalling, and the glycolytic pathway [1]. The efficacy of magnesium supplementation in improving glycemic control among non-diabetics [30, 31], pre-diabetics [32-34] and diabetics [23, 35, 36] has been suggested in some trials. A recent meta-analysis documented that magnesium is effective in decreasing the HOMA-IR index ( P = 0.013) but has no effect on glucose, HbA1c or insulin.…”
Section: Discussionmentioning
confidence: 99%
“…In another study, which used NHANES (1999)(2000)(2001)(2002)(2003)(2004), a 100 mg/d increase in Mg was associated with a reduced risk of MetSyn (8) . Randomised controlled trials (RCT) have shown that oral Mg supplementation of 250 and 365 mg/d for 3 and 6 months, respectively, reduced insulin resistance (9,10) , and Mg supplementation of 382 mg/d for 4 months improved blood pressure (BP), fasting plasma glucose and TAG (11) .…”
mentioning
confidence: 99%
“…The Mg deficiency might lead to a decrease in insulin mediated glucose uptake (Afridi et al, 2008;Lopez-Ridaura et al, 2004). The Mg supplementation prevented insulin resistance and also reduced the development of diabetes in animals (Mooren et al, 2011). The low level of Mg in the blood serum and an improved urinary excretion of Mg in the diabetics comparative to their healthy control subjects (Afridi et al, 2008).…”
Section: Mgmentioning
confidence: 99%